Exploring the Potential of Astaxanthin Extracted from Shrimp Shell Waste as a Functional Feed Additive in Duck Nutrition - Anwar, Rohimatul; Widyastuti Widyastuti; Annisa Ananda (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Shrimp shell waste is a potential marine biomass resource rich in bioactive compounds such as astaxanthin and chitin, yet remains underutilized in the livestock sector. This study aimed to evaluate the effect of incorporating shrimp shell meal into duck (Anas sp.) feed rations on the yolk color intensity of duck eggs. The experimental design applied a completely randomized design (CRD) with a single factor and four treatments: D0 (100% rice bran, control), A1 (rice bran + 2% shrimp shell meal), A2 (rice bran + 6%), and A3 (rice bran + 10%), with a 21-day observation period. The primary parameter measured was yolk color intensity, assessed visually using a standardized color scale. The results indicated that the addition of shrimp shell meal significantly enhanced yolk color intensity, with the highest pigmentation observed in the A3 treatment. Astaxanthin, functioning as a natural carotenoid pigment, was biologically absorbed and distributed into the yolk via lipophilic pathways, while chitin supported gut health and nutrient absorption efficiency. This study aligns with the principles of the circular economy by valorizing marine processing waste as a functional feed ingredient. A 10% inclusion rate was found to be visually optimal; however, further studies are required to assess its physiological impacts and economic feasibility in broader production contexts.